2020
DOI: 10.1002/ese3.801
|View full text |Cite
|
Sign up to set email alerts
|

Elastic modulus evolution of triaxially stressed mudstone at high temperature up to 400°C

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It can be noted that most research related to the effect of temperature on the shear behaviour of intact rocks were conducted on igneous rocks such as granite. While sedimentary rocks such as sandstone, limestone, and mudstone that are closely located above and below oil and gas reservoirs and coal beds 12 have received less attention. Moreover, clay-rich rocks such as mudstone are widely distributed in the earth's crust, accounting for approximately 30% of the surface rocks 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that most research related to the effect of temperature on the shear behaviour of intact rocks were conducted on igneous rocks such as granite. While sedimentary rocks such as sandstone, limestone, and mudstone that are closely located above and below oil and gas reservoirs and coal beds 12 have received less attention. Moreover, clay-rich rocks such as mudstone are widely distributed in the earth's crust, accounting for approximately 30% of the surface rocks 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These rock types have a great affinity for water due to the formation of a diffuse double layer around the negatively charged clay minerals, this makes the mechanical properties of these rocks unique and more complicated when exposed to temperature effects 15 17 . Some attempts were conducted to investigate the compressive and tensile behaviour of mudstone after thermal treatment 12 , 16 25 , and concluded that tensile and compressive properties improve to a certain temperature (400 and 600 °C) due to drying of clay minerals during thermal treatment, and then decrease after this limit. On the other hand, the effect of thermal treatment on shear behaviour of intact mudstone needs a comprehensive study and extensive efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Mudstone typically forms the upper and lower layers in sedimentary depos its, and it is characterized by its low permeability. In projects such as geologic al deep burial disposal of nuclear waste, geo-logical storage of CO2, high temp erature to reduce viscous oil extraction, and underground gasification/pyrolysis mining of coal, mudstone can be used as a containment layer to stop the migr ation of nuclides, oil and gas leakage, and contaminants [1][2][3]. The permeabilit y of mudstone stands as a critical parameter for governing fluid transport withi n these projects.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In such cases, when relatively low-temperature fluids (such as water and liquid nitrogen) make contact with high-temperature rocks, the drastic temperature changes are accompanied by the generation of thermal stress which deteriorates the mechanical properties of rock. [9][10][11][12] Consequently, it is imperative to understand the change in mechanical properties of high-temperature rock after cooling treatments. It can lay a solid theoretical foundation for increasing the production efficiency of geothermal well engineering applications or estimating the stability of the surrounding rock of tunnel postfire.…”
Section: Introductionmentioning
confidence: 99%
“…In certain circumstances, the reservoir rocks or surrounding rocks were initially in a high‐temperature environment or heated to extremely high temperatures before being subjected to rapid cooling treatment; for instance, in the process of the exploitation of HDR, cold drilling fluid is pumped into the wellbore to assist in rock breaking, and the liquid nitrogen is used in fracturing engineering, or when a conflagration occurs in the rock tunnel, and water‐based fire extinguishing agents are used to extinguish the fire 7,8 . In such cases, when relatively low‐temperature fluids (such as water and liquid nitrogen) make contact with high‐temperature rocks, the drastic temperature changes are accompanied by the generation of thermal stress which deteriorates the mechanical properties of rock 9–12 . Consequently, it is imperative to understand the change in mechanical properties of high‐temperature rock after cooling treatments.…”
Section: Introductionmentioning
confidence: 99%